O processo de trabalho do preso da Grande Vitória : a atividade laborativa extramuros - Menezes, Bruna Bolonha de (2015)
This research strives to analyze the process of external prison labor in Grande Vitoria (emphasizing the labor activity), discussing and revealing, above all, the external prison labor‘s peculiarities and characteristics and also the inmates‘ perception about their work. As a hypothesis, the research seeks to confirm (or not) that the external prison labor decreases some negative effects of thefact of being in jail. Therefore, the hypothesis, the study object and the objectiveswere clarified by the critical anal- ysis of the work category, according with Marx‘ theory, mainly regarding the centrality of the labor for the social being, wherewith the man is able to modify not only the na- ture, but himself and also the society. It was alsoconsider that, in Marx‘ analysis, the labor has a double determination over the merchandise, considering that the labor is essential in the capitalism, for example, for the creation of the surplus-value, which is a result of the exploitation of the work. The research goals were pursued by means of documental research, questionnaires, and Discussion Groups, besides interviews with the inmates from the semi-open regime of Grande Vitoria who practice external prison labor. 157 questionnaires and three interviews were applied and nine Discus- sion Groups were accomplished. The data analysis revealed that the external prison labor is, in general, precarious, flexible and intense, considering that the fact that the worker is in deprivation of liberty provides the intensification of the capitalist exploita- tion. Under the inmates‘ perspective, the labor appears also as: a way to restore daily practices; an escape from the constant imprisonment; a hope to have their penalties reduced, a possibility to help their relatives financially; and a desire to qualification and professionalization. From another perspective, the data, mainly the qualitative ones, showed that the initial hopes about the external prison labor are frustrated. Other fundamental data point to over-fulfilled penalties; unaccounted penalty reduc- tions; food shortages; in addition to the usual disregard with the inmates‘ physical and mental aptitudes. Those are a few issues that lead to an understanding regard- ing why, in the prison‘s language, the work at the semi-opened regime got to be called ―paid slave workǁ.